Effect of pH and current density on Nd-Fe-B thin films prepared by pulsed electrodeposition - Yeam, Chin Heng. (2009)
Ternary Iron Group (IG), Rare Earth (RE) alloys were codeposited from aqueous chloride solution with glycine acting as the complexing agent. The electrodeposition process was conducted with a dc current at ambient temperature in the absence of solution agitation. Variation of pH and current density (CD) on the morphology and magnetic properties of the resultant films were investigated using the Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray analysis (EDX), X-ray Diffraction (XRD) and Vibrating Sample Magnetometer (VSM).